ANALISIS HUBUNGAN KERJA KEPALA DESA DENGAN BADAN PERMUSYARAWATAN DESA DI DESA KOTO RANAH KECAMATAN KABUN KABUPATEN ROKAN HULU - Irawan, Zikri; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was motivated by two (2) partner institutions should run parallel and balanced in terms of thinking and decision-making that will affect and determine changes to a village, this institution has equal authority. The problem of this research is How the Employment Relations Village Head and Village Consultative Body in the village of Koto Ranah Kabun District of Rokan Hulu ? and this study aims to determine the employment relationship Village Head and Village Consultative Body (BPD) in the village of Koto subdistrict Sphere Kabun District Rokan Hulu. The population in this study are all government officials Desa, BPD and its members, and community leaders totaling 39 people, with details of Koto village government sphere 26, MRD Community Figures 5 and 8 people. This study uses census techniques, the entire population sample, which was then called the respondent. Data were collected through observation, questionnaires, interviews, and technical literature. In analyzing the data using qualitative descriptive analysis.In this study of all respondents who answered